Adverbials of time, time expressions and tense shifts in Alice Munro’s “Dance of the happy shades” - Težak, Katja (ELOPE (Ljubljana), 2022)
Alice Munro, the first female Canadian to have been awarded the Nobel Prize for literature, is a literary challenge and delight for the reader also with regards to the usage of references to time and their linguistic construction. Her literary work comprises short stories and one novel, which can more accurately be described as a short story cycle. She takes interest in everyday, small-town life and the human relationships in it, all described in concise, down-to-earth language. The settings in most of her stories are limited communities in a typically Canadian context. This paper deals with her short story “Dance of the Happy Shades” from the collection of the same name (1968), and focuses on a stylistic analysis of time expressions, tense shifts and adverbials of time. Munro has been praised for constructing moods of familiarity, home and small-town safety. The paper attempts to show that she achieves this not solely through the plot and themes, but also with the meticulous care with which she uses time expressions, time adverbials and tense shifts.
Keywords: "Dance of the happy shades"; adverbials of time; Alice Munro; časovni prislovi; izražanje časa; menjave slovničnih časov; stilistika; stylistic; tense shifts; time expressions